(untitled) (Eurasian Journal of Ecology, 2020)
The species diversity of the algoflora of five lakes, with different types of landscapes, located in the territory of the Almaty region was studied. The study covered five freshwater bodies includin: Balkhash, Alakol, Kolsay, Issyk and Big Almaty lake. Phytoplankton was studied for the first time in two lakes (Issyk and Big Almaty lake). The aim was to study the biodiversity of algoflora in lakes that are subject to various degrees of anthropogenic impact during recreational use. These water bodies are of great economic importance populations of the region, so the biological assessment of the water of these lakes is the most relevant. Analysis of the floral composition of the algoflora of lakes revealed a high species diversity of microalgae in all the studied objects. The highest quantitative and qualitative diversity in the lakes is represented by diatoms and green algae. The assessment of the ecological state of the water using microalgae as an indicator revealed that lake Balkhash is relatively dirty of all the studied lakes. Big Almaty lake, a high-altitude reservoir located in the reserve zone of the Trans-ili Alatau, was identified as the cleanest by saprobity. The scientific significance is to study the species diversity of microalgae and cyanobacteria of these objects. The practical significance is that the results obtained are necessary for forecasting and making recommendations for the conservation and normal functioning of natural complexes. Based on the results of the work of allocating pure cultures from samples taken from the lakes of the Almaty region received 5 algal pure cultures: Nephrochlamys sp., Ankistrodesmus falcatus, Monoraphidium griffthii, Parachlorella sp. и Monoraphidium sp. Key words: bioindication, algal flora, lakes Almaty region, microalgae, saprobity, algal pure cultures.